NorMAS-ML: Supporting the Modeling of Normative Multi-agent Systems - Freire, Emmanuel Savio Silva; Cortés, Mariela Inés; Da Rocha Júnior, Robert Marinho; Gonçalves, Ênyo José Tavares; De Lima, Gustavo Augusto Campos (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2019)
Context: A normative multi-agent system (NMAS) is composed of agents that their behavior is regulated by norms. The modeling of those elements (agents and norms) together at design time can be a good way for a complete understanding of their structure and behavior. Multi-agent system modeling language (MAS-ML) supports the representation of NMAS entities, but the support for concepts related to norms is somewhat limited. MAS-ML is founded in taming agents and objects (TAO) framework and has a support tool called the MAS-ML tool. Goal: The present work aims to present a UML-based modeling language called normative multi-agent system (NorMAS-ML) able to model the MAS main entities along with the static normative elements. Method: We extend the TAO adding normative concepts and spread out those concepts in two syntaxes of MAS-ML. Either abstract, adding or updating metaclasses and stereotypes or concrete, defining new graphic elements for representing the elements defined in the abstract syntax. Besides, we evolve the MAS-ML tool, considering the extension of MAS-ML by the model-driven approach. Results: NorMAS-ML, the new version of MAS-ML, allows a complete view of NMAS entities and has a support tool called NorMAS-ML tool. Beyond the definition of NorMAS-ML and its tool, we generate a new static diagram called “norm diagram” supported by the NorMAS-ML tool. In order to illustrate the syntax of NorMAS-ML, the entities of a conference management system and its norms are modeled jointly. Conclusion: NorMAS-ML can help software designers (i) to understand the properties and behavior of NMAS entities and (ii) to provide a software modeling following the stakeholders’ need and less complex for the development phase.